КОНЦЕПТ КАК СИНТЕЗ ЭЛЕМЕНТОВ ЯЗЫКА И КУЛЬТУРЫ. (Eurasian Journal of Philology Science and Education, 2015)
Мақалада мəдениет көзқарасы арқылы концепцияныңөзіндік ерекшелігі қарастырылады.The present article is dedicated to the linguistic andcultural problems of the concept.
Keywords: Лингвокультурологический концепт